Poisson-type approximation for sums of 1-dependent indicators - Petrauskienė, Jūratė; Čekanavičius, Vydas (Lietuvos matematikos rinkinys, 2009)
The sum of 1-dependent indicators is approximated by compound Poisson type distribution. Estimates are obtained for the uniform Kolmogorov and local metrics.
Keywords: m-dependent random variables; compound Poisson distribution; uniform Kolmogorov metric; local metric